The development of an Online Practical Application (OPA) system / Khazian Kassim - Kassim, Khazian (2006)
The faculty of Information Technology and Quantitative Sciences of Universiti Teknologi MARA for the past years has been using the traditional way or method in conducting the procedure regarding student's practical training. In the advanced world of technology and communication, this method was no longer considered efficient and effective due to several drawbacks that occur during the process. This thesis introduces Unified Modeling Language (UML-based) engineering fi-amework for the development of an Online Practical Application (OPA) System to give the overall view to the architecture of the system development. Therefore, four UML-based notation diagrams are used for the development, namely Use Case Diagrams, Sequence Diagrams, Collaboration Diagrams as well as Class Diagrams based on the real-world case study: Online Practical Application (OPA) System, using PHP and MySQL as the web-development tool to develop the intended system.